Pengelolaan Usaha Mikro Berbasis Kelompok Perempuan Desa Ngemplak II Yogyakarta - Weni Pratiwi, Monica; Arni Widyastuti, Dominica; Lucyanda, Jurica (Indonesian Journal for Social Responsibility, 2021)
The phenomenon of ever-increasing needs, such as the need for goods and services in household life, requires that people seek alternative income by producing processed food. However, to increase the processed food business, it does not only focus on the product aspect, but must also pay attention to marketing management and financial aspects so that this becomes the concern of the women's group of Ngemplak II village Umbulmartani Ngemplak Sleman Yogyakarta. The purpose of this Community Service is to provide training to women's groups to increase their understanding and ability to produce and develop processed food and use accounting to support the progress of their business. This activity provides an understanding of how to calculate product costs and prices (cost accounting), and accounting (financial aspect). In addition, the women's group was given training from marketing management aspect that how to make brands and register their product brands to the Directorate General of Intellectual Property Rights. Based on the results of the implementation of Community Service activities related to providing management training and financial empowerment programs for women in productive food management, there is enthusiasm from women's groups in Ngemplak II village Umbulmartani Ngemplak Sleman Yogyakarta. This Community Service Activity have been an impact on increasing knowledge in the field of small business management, especially in the field of trademarks and determining the price and break-even point. In addition, it also has an impact on knowledge about small business financial management, especially in the field of simple financial statement and profit and loss calculations, and also pricing.